ANALYSIS OF IMPLEMENTATION DELAYS USING THE EARNED VALUE METHOD (ON THE PURWOSARI - SEKARMOJO ROAD WORKS, PASURUAN DISTRICT) - Balido, Pandji Thoha S.; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2024)
Along with the very rapid development of infrastructure and construction in Indonesia in the era of globalization, the Indonesian government has carried out various large-scale projects to achieve the increasingly complex expectations of society. This will trigger the growth of the construction industry in Indonesia and become one of the main goals in the framework of national development. An infrastructure development project is an activity carried out with limited time and resources to achieve a specified final result. One of the construction projects currently being developed is Road Works. The Earned Value method can be used to determine cost performance and implementation time during the project and the indicators used for analysis include: BCWP (Budget Cost of Work Performance), BCWS (Budget Cost of Work Schedule), ACWP (Actual Cost of Work Performance), SV (Schedule Variance), CV (Cost Variance), SPI (Schedule Performance Index), CPI (Cost Performance Index), EAC (Estimated At Complete) and ET (Estimated To Complete) and TE (Time Estimate). Conclusions from this research is to determine the estimated costs and time for project completion. In the data analysis in the 9th week, the project schedule performance (CPI) was 1.14, greater than 1, while (SPI) was 0.587, less than 1. The results of the calculation of projected costs for the remaining work (ETC) were IDR. 1,586,686,537.62 and total project costs (EAC) of Rp. 2,509,041,243.08.